Reaffirming Indigenous data sovereignty in New Mexico as a result of COVID-19 - Carson, William O.; Cordova-Marks, Felina M.; Jennings, Lydia L.; Carroll, Stephanie Russo (Frontiers in Public Health, 2025)
Despite New Mexico’s history of working with and enhancing collaboration with the 23 Tribes in the state, data sharing and collaboration with Tribes was poor during the COVID-19 pandemic. New Mexico’s policies of state collaboration with Tribes conflicts with the principles of Indigenous Data Sovereignty and fails to recognize Tribal public health authorities. New Mexico state agencies limited what data Tribes and Tribal Organizations received, resulting in the suppression of Tribes’ inherent rights. This policy brief concludes with recommendations for the state of New Mexico to respect Tribal sovereignty, uphold the tenants of Indigenous Data Sovereignty, restore trust with Tribes, and support increased capacity and capability of Tribes.